Successful School Principals Balancing Ethical, Personal and Collective-A Norwegian Case - Hedvig Neerland Abrahamsen; Ann Elisabeth Gunnulfsen (MDPI AG, 2024)
Over the past two decades, there has been extensive research into what constitutes successful school principal leadership under the assumption that leaders' practices are significant and context-dependent on their school organization. By investigating how successful principals balance their personal ethical leadership dispositions and their intention of sharing leadership, this paper aims to contribute to the knowledge of how school principals need to balance the ethical, personal, and collective as the top leader of the school. Findings from the interviews suggested that a central aspect in the Norwegian school principals' characteristics of their leadership practices is student wellbeing and collaborative effort for school quality and student learning. Norwegian successful school principals seem to be relatively unaware of aspects of power use in their leadership practices. Dilemmas arise in the complexity of ensuring individual and collective effort and responsibility for the school to function in accordance with the societal mandate.